Distribution and Classification of Phosphorus Fractions and their relationship with Soil Properties in Ultisols of Meghalaya - Prashanta Kumar Patra; Luxmi Kant Tripathi, Arbind Kumar Gupta* (Journal of the Indian Society of Soil Science, 2021)
Ninety soil samples were collected from three depths of Barapani, Ri-Bhoi district, Meghalaya and determined phosphorus (P) fractions and their relationship with soil characteristics. The soils were acidic, low base saturated and rich in organic matter in the surface horizons. Majority of the soils was showing low cation exchange capacity (CEC), low bulk density, high available nitrogen (N), P and potassium (K). Among the P fractions, Fe-P was the most predominant followed by RS-P > Al-P > Occ-P > Ca-P > Sal-P. The overall results showed that the available P, organic-P and total-P decreased with increase in the soil depth, whereas Al-P, Fe-P, RS-P, Occ-P and Ca-P were found higher in lower horizons of the Ultisols. The Fe-P had positive correlation with clay (r = 0.45**) and negative with pH (r = -0.27**), EC (r = -0.34**) and available S (r = -0.29**). The Al-P was positively correlated with Fe-P (r = 0.332**), clay (r = 0.44**) and negative with OC (r = - 0.34**), CEC (r = -0.30**). Total-P and occluded-P were the main contributing factors for the availability of P. Multiple regression equations were also worked out for predicting different forms of P in relation to soil properties. Nutrient Index of available P for Ultisols was found under medium in category. About 60% soils of Ultisols are likely to respond of P- fertilizer.